Dynamics of Cost of Debt in Indonesia: The Interplay of Earnings Quality, Tax Avoidance, and Capital Structure in The Infrastructure and Property Sectors - Nur Aisyah Kustiani; Murtanto Murtanto (Universitas Negeri Padang, 2026)
This study examines the direct effects of earnings quality (EQ) and tax avoidance (TA) on the cost of debt (CoD), and explores the moderating role of capital structure (leverage) in Indonesia's infrastructure, property, and real estate sectors. Using a balanced panel of 103 listed companies (309 observations) from 2021 to 2023, we employ a robust Fixed Effects regression model. Earnings quality is proxied by the Stubben (2010) discretionary revenue model, while tax avoidance is measured using a transformed effective tax rate index (1 - ETR). The results reveal that earnings quality does not directly influence the cost of debt, reflecting a bank-based system where commercial lenders prioritize direct monitoring and physical collateral over public accounting metrics. However, tax avoidance exhibits a significant negative relationship with the cost of debt, strongly supporting the Tax-Saving Hypothesis where cash savings enhance internal liquidity and reduce default risk. Crucially, leverage significantly moderates the earnings quality–cost of debt relationship, proving that creditors value high-quality reporting as a vital monitoring mechanism only under elevated financial risk. Conversely, leverage does not moderate the tax avoidance–cost of debt link due to thin capitalization exemptions for infrastructure projects and flat final tax schemes for property firms. These findings offer practical insights for corporate executives optimizing capital structures and regulators refining financial disclosures.